Regulation of inflammatory response of macrophages and induction of regulatory T cells by using retinoic acid-loaded nanostructured lipid carrier. Issue 1 (2nd January 2019) - Zai, Khadijah; Ishihara, Narumi; Oguchi, Hiroyuki; Hirota, Masato; Kishimura, Akihiro; Mori, Takeshi; Hase, Koji; Katayama, Yoshiki
Abstract: Immunomodulatory function of all-trans retinoic acid (ATRA) has been gathering much attention for the therapy of autoimmune diseases. ATRA is a chemically unstable molecule which requires proper formulation for targeted delivery. Here we examined nanostructured lipid carrier (NLC) for the formulation of ATRA. NLC is a representative nanoparticle formulation especially suited for oral delivery. We established the preparation procedures of ATRA-containing NLC (NLC-RA) which minimizes the degradation of ATRA during the preparation process. NLC-RA thus obtained was taken up by macrophages and induced anti-inflammatory response via suppressing NF-κB signaling as well as via enhancing the production of anti-inflammatory cytokines. Moreover, NLC-RA enhanced differentiation of naïve T cells to regulatory T cells in the co-culture system with dendritic cells. These results suggest that NLC-RA is a promising alternative therapy for the autoimmune diseases especially intestinal bowel disease.